2007
DOI: 10.1111/j.1365-2486.2006.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic activity and biomass in Holocene permafrost deposits of the Lena Delta, Siberian Arctic and its implication for the global methane budget

Abstract: Permafrost environments within the Siberian Arctic are natural sources of the climate relevant trace gas methane. In order to improve our understanding of the present and future carbon dynamics in high latitudes, we studied the methane concentration, the quantity and quality of organic matter, and the activity and biomass of the methanogenic community in permafrost deposits. For these investigations a permafrost core of Holocene age was drilled in the Lena Delta (72122 0 N, 126128 0 E). The organic carbon of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…Moisture content, via its impact on organic matter preservation and anoxia, may exert a significant control on soil methanogen biomass and thus could influence rates of methanogenesis in various soils [52]. Corresponding trends have been observed between archaeal phospholipids and CH 4 concentrations in permafrost [23]. It should also be noted that methanogen viability is sustained in oxic conditions, thus it cannot be excluded that biomass distributions may not reflect absolute CH 4 production rates as oxygen suppresses methanogen capability rather than disrupting community structure [53, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moisture content, via its impact on organic matter preservation and anoxia, may exert a significant control on soil methanogen biomass and thus could influence rates of methanogenesis in various soils [52]. Corresponding trends have been observed between archaeal phospholipids and CH 4 concentrations in permafrost [23]. It should also be noted that methanogen viability is sustained in oxic conditions, thus it cannot be excluded that biomass distributions may not reflect absolute CH 4 production rates as oxygen suppresses methanogen capability rather than disrupting community structure [53, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Archaeal diether core lipids have been proposed as a methanogen biomarker or to estimate quantitatively methanogen biomass in natural systems. Respective studies have predominantly been restricted to highly anaerobic environments exhibiting significant CH 4 emissions such as rice paddies [16, 17], digester sludge [18, 19], marine sediment [20], faecal material [21], permafrost [22, 23], and peatlands [2426]. Wachinger et al [27] observed that absolute Archaea cell numbers in mineral soils, calculated using the approximate ether lipid concentration 2.5  μ mol g −1 dry weight of methanogen cells [28], also reflected CH 4 productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have addressed aspects of this issue in Siberia (for example [6], [8], [37]), Svalbard [19], [38] and the Canadian High Arctic [9]; [39] but the communities of the Canadian Western Arctic remain underexplored [40]. This study represents the first local-scale comparative microbiological analysis of polygonal tundra in the North-American Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…Low-center ice-wedge polygons, which are created by cryogenic processes associated with strong seasonal freeze-thaw cycles [5] typically have a depressed center and an elevated rim, creating a microrelief which affects the hydrology and organic carbon content of the soils. A thickening of the seasonally thawed layer (active layer) of polygons and an ensuing release of previously stored organic matter can stimulate microbial decomposition of this organic carbon, resulting in a positive feedback-loop for global warming [6]. Indeed, peat wetlands are an ideal environment for increased methane production because of the waterlogged, anoxic conditions that prevail in seasonally increasing thawed layers [7].…”
Section: Introductionmentioning
confidence: 99%
“…The presence and activity of methanogens has been reported from many subsurface environments on Earth, including the deep ocean (Cragg et al, 1996;Wellsbury et al, 2002;Colwell et al, 2008), permafrost (Kotsyurbenko et al, 2004;Wagner et al, 2007;Waldrop et al, 2010) and lake sediments (Ellis-Evans, 1984;Franzmann et al, 1991;Smith et al, 1993), promoted by a combination of anoxic conditions, a suitable carbon substrate and an absence of higher energy yielding electron acceptors. The release of this biogenic methane (CH 4 ) to the atmosphere is important in driving changes in global climate on geological, millennial and centennial timescales (Archer, 2007).…”
Section: Introductionmentioning
confidence: 99%